Stalkers and their victims - Mullen, Paul E. (Cambridge University Press, 2000)
Stalking has emerged as a major social issue over the past decade to become the subject of intensive clinical and research study. This volume combines the authors' extensive clinical experience working with stalkers and their victims with a critical and thorough review of the existing literature.